Chemical control of fall armyworm in field corn - Cruz, Ivan; Santos, Jamilton Pereira dos; Waquil, José Magid (Pesquisa Agropecuaria Brasileira, 2014)
Studies were performed on the effect of several insecticides on the control of fall armyworm, Spodoptera frugiperda (Smith), in field corn. Artificial infestation was achieved by using five second-instar larvae per plant before and after the insecticide application. Spray insecticide applications were made by using a coastal-manual sprayer with a pressure gage adapted permitting the pressure to be maintained at 40 psi. A regular flat fan nozzle number 8004 was used to direct the insecticide toward the inside of the plant whorl. Granular insecticides were applied to the plant whorl using a manual insecticide dispenser ("bazooka" type), It was concluded that the insecticides in granular formulation, such as chlorpyritos ethyl (Lorsban 15G), fonofos (Dyfonate 10G), methomyl (Lannate 5G), diazinon (Basudin 14G), decamethrin (Decis 0.1 G) and carbofuran (Furadan 5G), in an evaluation seven days after the insecticide application gave effective control of fall armyworms with a control rate of over 80%. Furthermore, these insecticides provided at least 5-days residual protection against the insect. Permethrin (Pounce) and methomyl (Lannate 90PS) were the best spray insecticides, when applied after infestation. However, their residual effects were low. Also, it was concluded that the granular insecticides were less affected by rainfall after their application than the insecticides applied in spray.
Keywords: pest control; Spodoptera frugiperda; artificial infestation; insecticides